La vigilance de l'autorité ecclésiatique. Visiter, veiller, surveiller - Bamberg, Anne (Monitor ecclesiasticus, 2015)
The author studies the canons of the (Latin) Code of Canon Law that deal with the power of the Ecclesiastical, authority to visit, monitor and watch the activities of the faithful in the hierarchical and associative institutions of the Church. She organizes her essay in three parts: 1) the pastors, i.e. the Supreme authority, the diocesan Bishops, the Metropolitans, and the Pastors have the duty and right to monitor, watch and make canonical visitations in many fields of Church's activity: teaching, sanctifying and governing. 2) The author gives a special attention to the vigilance on consecrated life, that diocesan Bishops have to exercise "with constant dialogue animated by charity", in order to help institutes and societies to live their own charism. 3) Finally, she deals with two fields in which the vigilance of the ecclesiastical authority is necessary: the vigilance on ecclesiastical jurisdiction and, as John Paul II's Motu Proprio Sacramentorum Sanctitatis Tutela and the following texts urged, the vigilance of the authority in order to prevent abuses and grave crimes, especially to protect minors